2004
DOI: 10.1111/j.1365-246x.2004.02251.x
|View full text |Cite
|
Sign up to set email alerts
|

Interferometric/daylight seismic imaging

Abstract: S U M M A R YClaerbout's daylight imaging concept is generalized to a theory of interferometric seismic imaging (II). Interferometric seismic imaging is defined to be any algorithm that inverts correlated seismic data for the reflectivity or source distribution. As examples, we show that II can image reflectivity distributions by migrating ghost reflections in passive seismic data and generalizes the receiver-function imaging method used by seismologists. Interferometric seismic imaging can also migrate free-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
259
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 388 publications
(265 citation statements)
references
References 32 publications
1
259
0
2
Order By: Relevance
“…The points x A and x B are chosen in D and both states have the same medium parameterŝ M A =M B =M. With these choices the correlation type Green's matrix representation is given bŷ (8) where the contrast functionM is Hermitian and given by…”
Section: Correlation Type Green's Matrix Representationmentioning
confidence: 99%
See 1 more Smart Citation
“…The points x A and x B are chosen in D and both states have the same medium parameterŝ M A =M B =M. With these choices the correlation type Green's matrix representation is given bŷ (8) where the contrast functionM is Hermitian and given by…”
Section: Correlation Type Green's Matrix Representationmentioning
confidence: 99%
“…Draganov et al [7] retrieved seismic subsurface reflections from noise records. Schuster et al [8] and Snieder [9] showed with stationary phase theory how not all sources on the boundary play an equally important role, but only those that are stationary for the resulting event. Wapenaar [10] showed that the elastodynamic response of an arbitrary heterogeneous elastic half space can be retrieved from contributions of sources in the subsurface below a pressure free surface.…”
Section: Introductionmentioning
confidence: 99%
“…Various theories have been developed to explain this phenomenon, ranging from diffusion theory for enclosures [Weaver and Lobkis, 2001], multiple scattering theory and stationary-phase theory for random media [Malcolm et al, 2004;Snieder, 2004] and reciprocity theory for deterministic and random media [Wapenaar, 2004;Weaver and Lobkis, 2004;van Manen et al, 2005]. The principle of recovering an acoustic response by cross-correlation is often called Green's function retrieval; in the geophysical literature it is also known as seismic interferometry [Schuster et al, 2004;Wapenaar and Fokkema, 2006;Snieder et al, 2006].…”
Section: Introductionmentioning
confidence: 99%
“…This type of configuration occurs for example in exploration seismology, where the sources are located at the earth's surface only. For this configuration cross-correlation methods have been developed by Schuster et al [2004] as a method for seismic imaging, by Bakulin and Calvert [2004] for Green's function retrieval and by Verschuur and Berkhout [2005] for transforming surface related multiples into primaries. Impressive results have been obtained by these authors for ballistic waves, but the coda due to internal multiple scattering was not considered.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, passive sources are used such as mini earthquakes within the subsurface of the earth ͑for example, from reservoir rocks cracking due to fluid-pressure changes during production͒ or heavy traffic on the surface. We will compare the passive data model with the primary-multiple model and demonstrate that crosscorrelating data, as is usually done in seismic interferometry ͑see, e.g., Claerbout, 1968;Schuster, 2001;Shapiro and Campillo, 2004;Wapenaar, 2004;Wapenaar et al, 2004;Snieder et al, 2006;Dellinger and Yu, 2009;Draganov et al, 2009͒, is only the first step in a modified version of the recently introduced estimation of primaries by sparse inversion ͑EPSI͒ method ͑van Groenestijn and Verschuur, 2009a͒. A framework to describe active and passive seismic data ͑Berkhout and Verschuur, 2009͒ proposes to find the primary impulse responses via an inversion method.…”
Section: Introductionmentioning
confidence: 99%